Respostas
respondido por:
0
Resposta:
Explicação passo-a-passo:
a13 = a3+10r
a13= 2 + 10.3
a13= 32
respondido por:
0
Resposta:
. a13 = 32
Explicação passo-a-passo:
.
. P.A., em que:
.
. a1 = - 4 e a2 = - 1 a13 = ?
. razão = a2 - a1
. = - 1 - (- 4)
. = - 1 + 4
. = 3
.
Termo geral: an = a1 + (n - 1) . razão
n = 13 ==> a13 = - 4 + (13 - 1) . 3
. = - 4 + 12 . 3
. = - 4 + 36
. = 32
.
(Espero ter colaborado)
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás